Statistical model of caries formation and progression in children of preschool and early school age domiciled in biogeochemical deficiency of fluorine and iodine - Klitynska, Oksana; Gasyuk, Natalia; Kostenko, Yevgen; Gurando, Viacheslav (Journal of Stomatology, 2017)
Aim of the study. To create a statistical and prognostic model of caries formation and progression in children of preschool and early school age domiciled in biogeochemical deficiency of fluorine and iodine. Materials and methods. Microbial landscape was identified with biochemical parameters and immunological status of saliva in 146 children aged 3-8 years of different ethnic groups. Statistical evaluation of the results was conducted. Conclusions. For the formation and progression of caries the presence of Str. sobrinus is necessary plus dysbiotic changes in the oral cavity (decrease of concentrations of Bifidobacterium and Lactobacillus salivarius, emergence of conditionally pathogenic and pathogenic microorganisms), increasing concentration of ionized calcium, alkaline phosphatase, and lower levels of phosphorus and pH.